2011
DOI: 10.1038/jid.2010.377
|View full text |Cite
|
Sign up to set email alerts
|

RANK Is Expressed in Metastatic Melanoma and Highly Upregulated on Melanoma-Initiating Cells

Abstract: Melanoma accounts for ∼ 79% of skin cancer-related deaths, and the receptor activator of NF-κB (RANK)-receptor activator of NF-κB ligand (RANKL) pathway has been shown to be involved in the migration and metastasis of epithelial tumor cells. In this study, we demonstrate that RANK was significantly increased in peripheral circulating melanoma cells, primary melanomas, and metastases from stage IV melanoma patients compared with tumor cells from stage I melanoma patients. However, upregulated RANK expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 33 publications
5
51
0
1
Order By: Relevance
“…77 Most recently, melanoma cells that expressed the receptor activator of NF-kB (RANK) demonstrated enhanced tumorigenicity compared with RANK-negative melanoma cells in IL-2Rg À/À NOD/SCID mice. 78 Moreover, RANK was coexpressed with ABCB5 and CD133 on melanoma cells, and preferentially expressed by peripheral circulating melanoma cells, primary melanomas, and metastases from stage IV melanomas compared with stage I melanoma patients. 78 SKEPTICISM REGARDING MELANOMA STEM CELLS Soon after the identification of ABCB5 as a melanoma stem cell marker, the existence of cancer stem cells in human melanoma was questioned.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Most recently, melanoma cells that expressed the receptor activator of NF-kB (RANK) demonstrated enhanced tumorigenicity compared with RANK-negative melanoma cells in IL-2Rg À/À NOD/SCID mice. 78 Moreover, RANK was coexpressed with ABCB5 and CD133 on melanoma cells, and preferentially expressed by peripheral circulating melanoma cells, primary melanomas, and metastases from stage IV melanomas compared with stage I melanoma patients. 78 SKEPTICISM REGARDING MELANOMA STEM CELLS Soon after the identification of ABCB5 as a melanoma stem cell marker, the existence of cancer stem cells in human melanoma was questioned.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
“…78 Moreover, RANK was coexpressed with ABCB5 and CD133 on melanoma cells, and preferentially expressed by peripheral circulating melanoma cells, primary melanomas, and metastases from stage IV melanomas compared with stage I melanoma patients. 78 SKEPTICISM REGARDING MELANOMA STEM CELLS Soon after the identification of ABCB5 as a melanoma stem cell marker, the existence of cancer stem cells in human melanoma was questioned. Data were presented indicating that tumor-initiating cells in melanoma might not be as rare as had been previously believed and that non-stem cells may also be tumorigenic.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
“…Recent studies suggested an involvement of RANKL in disease pathophysiology of chronic lymphoid leukemia (CLL) and multiple myeloma as well as metastatic spread of solid tumors (19)(20)(21)(22)(23)(24)(25)32), but nothing was yet known on the role of the RANK-RANKL molecule system in AML. In this study, we analyzed RANKL expression on primary AML cells by flow cytometry and selected malignant cells among PBMCs of leukemia patients by staining for CD33 and CD34.…”
Section: Expression Of Rankl In Amlmentioning
confidence: 99%
“…More specifically, highly tumorigenic melanoma stem/progenitor cells have been identified in situ and isolated from primary and secondary melanoma tumors, circulating melanoma cells and established melanoma cell lines [20,21,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] . Melanoma stem/progenitor cells may express different stem cell-like markers such as CD133, nestin, aldehyde dehydrogenase (ALDHhigh ), CD166, neural crest nerve growth factor receptor (CD271) and/or ATP-binding cassette (ABC) multidrug resistance transporters such as multidrug resistance-1 encoding P-glycoprotein (P-gp), ABCG2 and ABCB5.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma stem/progenitor cells may express different stem cell-like markers such as CD133, nestin, aldehyde dehydrogenase (ALDHhigh ), CD166, neural crest nerve growth factor receptor (CD271) and/or ATP-binding cassette (ABC) multidrug resistance transporters such as multidrug resistance-1 encoding P-glycoprotein (P-gp), ABCG2 and ABCB5. It has been shown that highly tumorigenic melanoma stem/progenitor cells can give arise to the total tumor cell mass in vivo with the phenotypic features resembling to original patient's melanomas and metastasize at distant sites [50][51][52][53][54][55][56][57][58]60,61,[63][64][65] . In this matter, we review the most recent advancements on the gene products that are often altered during melanoma initiation and progression to locally invasive and metastatic disease states and which may be exploited to develop novel multiplex biomarker detection methods for optimizing diagnosis and prognosis and multitargeted therapies for a more effective management of melanoma patients.…”
Section: Introductionmentioning
confidence: 99%